Impact of Storage Conditions and Premix Type on Fat-Soluble Vitamin Stability - M. Saensukjaroenphon; C. E. Evans; C. K. Jones; J. T. Gebhardt; J. C. Woodworth; C. R. Stark; J. R. Bergstrom; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2020)
The objective of Exp. 1 was to determine the impact of 0, 30, 60, or 90 d storage time on fat-soluble vitamin stability when vitamin premix (VP) and vitamin trace mineral premix (VTM) are blended with 1% inclusion of medium chain fatty acids (MCFA; 1:1:1 blend of C6:C8:C10) or mineral oil (MO) with different environmental conditions. Treatments were arranged as a 2 × 2 × 2 × 4 factorial, with 2 premix type (VP or VTM), 2 oil type (MO or MCFA), 2 storage conditions [room temperature (RT) or high-heat, high-humidity (HTHH)] and 3 storage times (30, 60, or 90 d). Samples were stored at room temperature in a temperature-controlled laboratory (approximately 72°F) for RT or in an environmentally-controlled chamber set at 104°F and 75% humidity for HTHH. For Exp. 1, there was a premix type × oil type × storage time interaction of vitamin A (P = 0.002). Vitamin A was stable in VP mixed with MCFA and VTM mixed with MO when stored from 0 to 90 d. Increasing the storage time continued to degrade vitamin A in VP mixed with MO and VTM mixed with MCFA. There was a premix type × storage condition interaction (P<0.01). When premixes were stored under HTHH, the VTM had greater vitamin A stability as compared to VP. However, there was no difference for vitamin A stability between VP and VTM when stored under RT. There was an oil type × storage condition interaction (P<0.01). The premixes with MO had a higher vitamin A stability compared to the premixes with MCFA when stored at RT. However, there was no difference for vitamin A stability between premix with MO and MCFA when stored at HTHH. There was a storage condition × time interaction (P<0.01). When premixes were stored at HTHH, the vitamin A stability decreased as storage time increased to d 90. However, there was no difference in vitamin A stability as storage time increased to d 90 when stored at RT. Vitamin D3 stability was increased (P<0.002) when stored at RT compared to premixes stored at HTHH. There was a decrease in vitamin D3 stability as storage time increased (P = 0.002) from d 30 to 60; however, there was no further decrease from d 60 to 90. There was a storage condition × time interaction (P<0.001) for vitamin E stability. Vitamin E was stable at both RT and HTHH up to 30 d. However, the degradation rate of vitamin E was faster when premixes were stored under HTHH versus RT after 30 d of storage. The objective of Exp. 2 was to determine the effect of d of MCFA addition and premix type on fat-soluble vitamin stability after exposure to a heat pulse process. Treatments consisted of a 2 × 2 factorial, with 2 premix types (VP or VTM) and 2 oil types (MO or MCFA). All treatments were heated in an environmentally-controlled chamber at 140°F and 20% humidity. Vitamin A stability was reduced (P= 0.030) in premixes containing MCFA after premixes were heated at 140°F. The premix type did not affect the stability of vitamins A and D3. However, after the heat pulse treatment, vitamin E stability was reduced (P= 0.030) in VP compared to VTM.
Keywords: vitamin stability; vitamin storage; premix stability